THE DEVELOPMENT OF A TRADITIONAL GAME HANDBOOK FOR GROWING THE CHARACTER OF JUSTICE IN CHILDREN 6-8 YEARS OLD - Joshephin Epsilona Yustisia; Nugrahanta, Gregorius Ari (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
This study aimed to develop a traditional game manual to improve the character of justice for children aged 6-8 years. This study was conducted with ADDIE type of research and development (R & D) method. Seven teachers from various regions for need analysis, ten validators for expert judgement, and six children for a preliminary field testing participated in this study. The results showed 1) The traditional game manual was developed according to the stages of ADDIE type, namely Analyze, Design, Develop, Implement, and Evaluate; 2) The quality of the traditional game manual was in the “Very good” category equivalent to a score of 3,96 (Scale 1-4) with the recommendation “No need for revision”; and 3) The application of the manual effected on children’s justice character. The significance test showed t(5) = 9.010; p < 0.05. The effect size was r = 0,97 which was included in the “big effect” category od equivalent to 94,20%. It meant that the implementation could explain 94,20% of variance changes in justice characters. The test for the effectiveness of the manual showed N-Gain Score of 76,03% equivalent to the “High” category.